Rice-based Cropping System Intensification in the Coastal Saline area of Bangladesh: Problems and Prospects (Bangladesh Rice Journal, 2023)
The coastal zone environment of Bangladesh is characterised geographically by river deltas and estuaries, where tidal and riverine flooding and varying salinity levels affect agriculture and livelihoods. In this area, the land and agricultural productivity is very low because of several constraints, particularly waterlogging, high salinity of soil and water, freshwater scarcity for crop irrigation and natural disaster. In this review, the objectives are to focus on the limiting factors for crop intensifying and highlighting the opportunities to increase coastal agriculture while enhancing farmer’s livelihoods. Some recent studies demonstrated many opportunities for increasing cropping systems that have not yet been exploited extensively. Rainwater or low saline river water storing in the internal canal can fulfil the water requirement for dry season rice and non-rice crops, thereby increasing growth and yield. Early establishment of “Rabi” crops (non-rice) can utilize maximum low-saline soil water and escape high salinity/drought or heat/storms at later period of the growing stages, but this early sown Rabi crops needs early harvest of Aman rice around 15-30 days earlier than farmer practices. Moreover, early sowing by zero tilled dibbling (such as sunflower, maize, wheat, and potato) in wet soils results in higher yield potential. Using rice straw mulch ~5 t ha-1 has been shown to be highly beneficial for ameliorating soil constraints. A recent study revealed that straw mulch application on soil surface increased soil water and soil solute potential in the upper root zone, reduced soil salinity, soil strength, and cracking which attributed to higher yield. Considering the successful dry season crop establishment and yield potential requires early drainage to remove excess soil water and a drainage system that mitigates waterlogging from heavy rainfall events during the growing season. We expect this review will facilitate the future research planning and execution in this vulnerable coastal environment.Bangladesh Rice J. 25 (2) : 31-43, 2021